Os índices de confiança ajudam a elaborar previs\~oes econômicas confiáveis? - Emilio Chernavsky (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper intents to empirically verify whether some of the confidence indexes more popular in Brazil have effectively been useful in recent years to build reliable forecasts on the evolution of key indicators of economic activity, as well as evaluate the impact of the rapid reversion of the indexes in May 2016 on the reliability of those forecasts. With this aim a series of simple econometric models was estimated, including and excluding the period after that reversion, relating the evolution of activity indicators to that of the confidence indexes alone and, afterwards, also to a set of traditional macroeconomic indicators, assessing the joint significance of the parameters and the adjusted adjusted ² coefficient. The results showed the analyzed indexes are indeed able to contribute to the building of forecasts on the evolution of industrial production and retail sales. However, this contribution is very heterogeneous variating depending on the index being considered and, generally, relatively low, what, associated to the reduced size of the samples, recommends caution in the interpretation of the forecasts built on them. Such a caution is even more needful in moments like 2016, when the change in the indexes with no similar movement in the activity indicators reduced its predictive power in most of cases.
Keywords: D84; E27; 330; confidence indexes; macroeconomic forecasting